O Museu Solar Monjardim como mediador dos processos educativos - Abdon, Jorge Luiz (2024)
This research was developed together with the Postgraduate Professional Master’s Program in Education, at the Federal University of Espírito Santo and is linked to the Teaching and Management of Educational Processes research line. Its main objective was to analyze in the narratives of monitors and teachers of museum that permeate the educational proposals of the Museu Solar Monjardim (MSM), as well as the production of meanings and knowledge in the partnership relationship with institutionalized education. To this end, field research was carried at the MSM located in Vitória-ES, to learn about the educational activities developed. The field research experiences at the museum also served to simultaneously carry out interviews about the monitors’ actions with the general public. In addition, a search and listening was carried out by Basic Education educators who were at the museum in 2023, seeking to understand how their work developed with the students after visiting the museum. The justification for choosing the theme the lies in the learnig that can begin with individual stories located in a collective history. These characteristics of the museum were also identified when we carried out the State of Knowledge. It was noticed how much a museum contributes to the training of students and how it produces feelings of belonging. The theoretical framework in this research includes Pereira (2011), Chagas (2016) and Ramos (2004) who discuss the issue of Education in museums. Field research consists of the following procedures: a) interviews with employees from the MSM educational sector and teachers who visited the MSM in the first half of 2023; b) observations of activities carried out within the MSM. Based on the assumptions of Oral History, the thematic interviews revealed that the MSM presents itself in a contemporary way, despite bearing the name of a wealthy family in the 18th and 19th centuries. The teachers interviewed called for renewal, felt elitism and demanded a democratic call through more publicity of the institution and collections. But even só, the MSM is willing to listen and interact with students who carry out field studies there.